Systemic uptake, albumin and hemoglobin binding of [14C]2, 3-butanedione administered by intratracheal instillation in male Harlan Sprague Dawley rats and oropharyngeal aspiration in male B6C3F1/N mice. (5th February 2015) - Fennell, Timothy R.; Morgan, Daniel L.; Watson, Scott L.; Dhungana, Suraj; Waidyanatha, Suramya
Highlights: 2, 3-Butanedione plays a major role in obliterative bronchiolitis in workers in microwave popcorn manufacturing. BD enters systemic circulation following intratracheal instillation in rats and oropharyngeal aspiration mice. Significant fraction of systemic dose was bound to hemoglobin and albumin to form adducts. One of the major sites of adduction was on arginine residues. Abstract: 2, 3-Butanedione (BD) is a reactive diketone in artificial butter flavors that is thought to cause bronchiolitis obliterans in workers in microwave popcorn manufacturing. Bronchiolitis obliterans is generally not diagnosed until irreversible damage has occurred; therefore a biomarker of early exposure is needed. The potential systemic uptake of BD from inhalation exposure has not been evaluated. The objective here was to evaluate the systemic exposure of BD and binding to hemoglobin and albumin. [ 14 C]BD was administered to male Harlan Sprague Dawley rats (100 mg/kg, intratracheal instillation) and B6C3F1/N mice (157 mg/kg, oropharyngeal aspiration). Blood and plasma was collected 24 h after administration and analyzed for 14 C content. At 24 h, 0.88 ± 0.07% of the administered dose was in rat blood, 0.66 ± 0.06% in rat plasma, 0.38 ± 0.13% in mouse blood and 0.17 ± 0.05% in mouse plasma. Albumin binding in rats was 269 ± 24.2 ng equiv./mg, which accounts for 38% of the radioactivity in plasma. In mice, binding was 85.0 ± 22.3 ng equiv./mg albumin, which accounts for 51% of the radioactivity in plasma. The binding to hemoglobin in rats was 38.2 ± 17.6 ng equiv./mg, and to globin was 29.1 ± 3.96 ng equiv./mg. In mice, the binding to hemoglobin was 16.2 ± 9.0 ng equiv./mg. The site(s) of adduction on hemoglobin and albumin was investigated by mass spectrometry. In rat globin, arginine adducts were detected at R-30 and R-104 of the beta chain in vitro and in vivo. In rat albumin, adducts were detected in vitro on R-219/221, R-360, and R-368, and in vivo on a variety of arginine residues. This study demonstrated that BD enters the systemic circulation and reacts with arginine on hemoglobin and albumin. These results indicate that hemoglobin and albumin adducts may be useful as biomarkers of BD exposure in humans.